Expression of ovate family protein 8 affects epicuticular waxes accumulation in Arabidopsis thaliana - Yao Tang (Botanical Studies, 2018)
Abstract Background Transcription factors could regulate multiple aspects of plants growth and development, which is significant to plants. Ovate family proteins (OFPs) that are named due to contain OVATE domain, a 70-AA C-terminal conserved domain from the protein OVATE gene encodes, are plant-specific transcription factors family. Some members of OFPs have been shown to function as transcription factors to regulate plant growth and development, but little is known about the function of AtOFP8. Results Here, we found AtOFP8 maybe involve in transcriptional regulation of the epicuticular waxes in Arabidopsis thaliana. First, we observed that the distribution of epicuticular waxes of wild type plants was more than that of Atofp8-1 deletion mutants, but less than that of 35S:HA-AtOFP8 transgenic overexpression lines not only on the leaves but also on the stems utilizing scanning electron microscopes. Second, we extracted waxes from leaves and stems of three types of plants respectively to measure the waxes content and composition by gas chromatography–mass spectrometer (GC–MS), and the results of the total content of waxes were consistent with the results of scanning electron microscopes. Finally, we found that the expression of 12 genes related to the synthesis and metabolism of waxes was changed in the Atofp8-1 mutants and 35S:HA-AtOFP8 transgenic lines compared with wild type plants. Conclusions These findings suggest that AtOFP8 could change the accumulation of epicuticular waxes.